Readiness for Future Health Professional Collaboration: Knowledge of Interprofessional Collaboration among Undergraduate Health Students - Risnah; Asrul, Nur Al Marwah; Alwi; Irwan, Muhammad; Harmawati (Bantayang Omni Cendekia, 2026)
Background: Interprofessional collaboration (IPC) refers to cooperation among health workers from different professional backgrounds in providing comprehensive health services involving patients, families, and communities to ensure optimal quality of care. Adequate knowledge of IPC among health students is essential as a foundation for effective collaborative practice in the future. Objective: This study aimed to describe the level of knowledge of prospective health undergraduate students regarding interprofessional collaboration. Methods: This study employed a non-experimental quantitative design with a descriptive approach. A total of 50 prospective health undergraduate students were selected using quota sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics. Results: The findings showed that the majority of respondents demonstrated a good level of knowledge regarding interprofessional collaboration. High levels of knowledge were observed in understanding the definition and benefits of IPC (both 86%). However, lower proportions of respondents demonstrated good knowledge regarding the objectives, factors influencing, and barriers to IPC, with good knowledge levels ranging from 50% to 60%. Conclusion: Although prospective health undergraduate students generally possess good foundational knowledge of interprofessional collaboration, gaps remain in understanding its practical objectives, influencing factors, and barriers. Future research is recommended to not only assess knowledge levels but also evaluate students’ readiness and competencies in implementing interprofessional collaboration in clinical practice.